2016
DOI: 10.1002/bio.3224
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnSe and ZnSe:Cu quantum dots by a room temperature photochemical (UV‐assisted) approach using Na2SeO3 as Se source and investigating optical properties

Abstract: In this study, ZnSe and ZnSe:Cu quantum dots (QDs) were synthesized using Na SeO as the Se source by a rapid and room temperature photochemical (UV-assisted) approach. Thioglycolic acid (TGA) was employed as the capping agent and UV illumination activated the chemical reactions. Synthesized QDs were successfully characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), photoluminescence (PL) and UV-visible (UV-vis) spectroscopy, Fourier transform-infrared (FT-IR), and energy dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…The PL spectrum of QDs is a broad emission spectrum with three peaks located at 400 nm, 435 nm and 460 nm. Such phenomenon had been reported by previous investigation [35] . The first peak at 400 nm is attributed to band gap emission.…”
Section: Resultssupporting
confidence: 87%
“…The PL spectrum of QDs is a broad emission spectrum with three peaks located at 400 nm, 435 nm and 460 nm. Such phenomenon had been reported by previous investigation [35] . The first peak at 400 nm is attributed to band gap emission.…”
Section: Resultssupporting
confidence: 87%
“…[52] The band at 1645 cm À 1 is attributed to the COO À bonds. [53] Raman spectra represent the structural data about the sample in the form of chemical bonds and atomic rearrangements. The Raman spectra of CuZnSe-1, 2 samples are shown in Figure 2(d).…”
Section: Structural Analysis: Xrd Ftir and Ramanmentioning
confidence: 99%
“…The uniform size of the QDs was achieved using the HI method, which absorbed significant amounts of UV light and converted it into visible light. The emission spectra contained three different peaks at 400 nm, 435 nm, and 460 nm, which were attributed to the bandgap emission, surface trap state, and deep level state of the QDs, respectively [ 197 ]. The results revealed that the cell with QDs exhibited a PCE of 17.3% as well as better stability compared to the cell without QDs.…”
Section: Qds With Various Solar Cellsmentioning
confidence: 99%